Rhetoric and Reality in the English National Health Service; Comment on "Who Killed the English National Health Service?" - Rudolf Klein (Kerman University of Medical Sciences, 2015)
Despite fiscal stress, public confidence in the National Health Service (NHS) remains strong; privatisation has not hollowed out the service. But if long term challenges are to be overcome, pragmatism not rhetoric should be the guide.